Impact of scapholunate dissociation on human wrist kinematics. (February 2018) - Stromps, J. P.; Eschweiler, J.; Knobe, M.; Rennekampff, H. O.; Radermacher, K.; Pallua, N.
Neither the complex motions of the scapholunate joint, nor the kinematic changes that occur as a result of injury to it, are fully understood. We used electromagnetic tracking within affected bones to evaluate the physiologic motions in the planes of flexion and extension, and of radial and ulnar deviation of human cadaver wrists, before and after complete transection of the scapholunate ligaments. Despite individual variance between each wrist, we were able to establish a pattern in the changes that occurred after scapholunate ligament injury. During the motions examined, the scaphoid showed an increase in translational deviation in almost all motion axes. In contrast, the movement of the lunate seemed to be impaired, especially in radial-ulnar deviation.